DIAGNOSTICS OF NOSOCOMIAL PNEUMONIA IN THOSE WITH MULTIPLE TRAUMAS (BASING ON DATA OF FOREIGN PUBLICATIONS) - A. V. Prokhorov; Yu. Sh. Khalimov; S. V. Gayduk; S. V. Gavrilin; D. P. Meshakov; A. I. Chepel (Вестник анестезиологии и реаниматологии)
Trauma is one leading cause of death in young patients under 45 years old and it occupies the third pace among causes of general mortality for the whole population. Nosocomial infections (first of all ventilator-associated pneumonia) account for mortality in this group of patients in 5 days after trauma. The article describes risk factors, causative agents, pathologic physiology and specific features of diagnostics of nosocomial pneumonia in those with multiple traumas. Special attention is paid to immune response of the host to multiple trauma and related issues on using polymorphism of genes controlling production of certain cytokines in order to improve diagnostics and prognosis of the course and outcome of nosocomial pneumonia in this group of patients.